Civil Servant Performance and Organizational Effectiveness from the Ministry of Tourism and Creative Economy of Indonesia - Laila, Nur; Asropi, Asropi (Pusjar SKPP Lembaga Administrasi Negara, 2026)
The purpose of this study is to explain the causes of problems that occur in the performance assessment of ASN employees at the Ministry of Tourism and Creative Economy/Tourism and Creative Economy Agency by using Kaswan's theory on the elements of performance assessment, namely that performance assessment can be said to be ideal if it contains performance standards, measurable performance measures, and no assessment errors occur. Based on these elements, the author then formulates a problem-solving strategy. This study uses a qualitative approach with data collection methods through in-depth interviews and documentation studies. The collected data are then processed through data reduction, presentation, and conclusion drawing. Based on the results of the study, it was concluded that the performance evaluation did not use clear performance standards; the Employee Performance Target (SKP) document listed no clear performance measures; and there were still assessment errors closely related to the element of leadership subjectivity. The author's strategy is to change the performance assessment method to a 360-degree system, so that performance can be assessed more objectively, as it is seen from various evaluators.